Sustainable aluminium recycling of end-of-life products: A joining techniques perspective. (20th March 2018) - Soo, Vi Kie; Peeters, Jef; Paraskevas, Dimos; Compston, Paul; Doolan, Matthew; Duflou, Joost R.
Abstract: The sustainable management of aluminium has become crucial due to the exponential growth in global demand. The transition to a sustainable society with lightweight electric vehicles has led to the increasing use of aluminium in the transportation sector. This has consequently led to the importance of aluminium recycling to prevent the valuable material stream going to landfill. In addition, the extraction of primary aluminium has high environmental impact due to the high energy consumption and waste generation in comparison to secondary aluminium processing. Despite being one of the most recycled metals, ongoing trends of multi-material designs and the associated joining choices have caused increasing difficulty of separating aluminium with high purity. This paper evaluates the types of joining techniques causing impurities in the aluminium streams, and the relationship between particle size reduction and the presence of impurities due to joints particularly for end-of-life vehicles. An empirical experiment in a leading European recycling facility was conducted and demonstrated that mechanical fasteners, such as machine screws, socket screws, bolt screws and rivets, are the major types of joining technique causing impurities. Based on the observations from this case study, the characteristics of imperfectly liberated joints are examined. A Life Cycle Assessment (LCA) is also performed to evaluate the environmental impact of recycling different aluminium scrap qualities with varying impurity levels. The outcomes are then used to provide ecodesign guidelines aimed at improving the quality and increase the quantity of recycled aluminium. Highlights: Identified the types of joining techniques causing impurities in the Al streams. Characterised the joints causing Fe impurities in the Al streams. Recycling efficiency of Al was measured through an industrial trial in Europe. Identified the linkage between particle sizes and impurities due to joints. Assessed the environmental impact of dilution and quality losses due to joints.